2014
DOI: 10.1111/isqu.12129
|View full text |Cite
|
Sign up to set email alerts
|

Responding to Voters or Responding to Markets? Political Parties and Public Opinion in an Era of Globalization

Abstract: Conventional wisdom has it that political parties have incentives to respond to public opinion. It is also conventional wisdom that in open economies, policymakers must also "respond" to markets. Research on representation has provided ample evidence in support of the first claim. Research on the political economy of globalization has not, however, provided evidence for the second. This article examines the effects of globalization on how parties respond to voters. We argue that while elections motivate partie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 58 publications
3
83
1
Order By: Relevance
“…However, other recent research on party responsiveness to citizen preferences has shown that in certain contexts parties are less responsive. Ezrow and Hellwig (2011), for example, demonstrate that, as parties become further integrated into world markets, they become less responsive to the electorate. These findings also concur with Wu¨st and Schmitt's (2007) analysis of Euromanifestos from the 1999 EP elections.…”
Section: Resultsmentioning
confidence: 99%
“…However, other recent research on party responsiveness to citizen preferences has shown that in certain contexts parties are less responsive. Ezrow and Hellwig (2011), for example, demonstrate that, as parties become further integrated into world markets, they become less responsive to the electorate. These findings also concur with Wu¨st and Schmitt's (2007) analysis of Euromanifestos from the 1999 EP elections.…”
Section: Resultsmentioning
confidence: 99%
“…4 The implication 4 Note, however, the large literature on how market openness affects public policy and whether it constrains the actions of governments (e.g., Garrett 1998;Swank 2002;Clark 2003;Basinger and Hallerberg 2004;Steinmo 2010), a more recent literature that notes effects of open markets on party positions (e.g., Haupt 2010;Adams, Haupt, and Stoll 2009;Ward, Ezrow, and Dorussen 2011;Ezrow and Hellwig 2014), and some studies pointing to external influences on parties'…”
mentioning
confidence: 99%
“…If public opinion moves right, for example, parties' preferences will follow (see e.g. Adams et al, 2004Adams et al, , 2006Ezrow and Hellwig, 2014). Adams et al (2004) specifically find that parties are more responsive to voters when their preferences shift away from the party's policy positions.…”
Section: Party Responsiveness To Euroskepticismmentioning
confidence: 99%
“…Adams et al, 2004Adams et al, , 2006Ezrow and Hellwig, 2014). Importantly, however, responsiveness is not uniform.…”
Section: Introductionmentioning
confidence: 99%